Oncolytic HSV infected glioma cells activate NOTCH in adjacent tumor cells sensitizing tumors to gamma secretase inhibition. - Otani, Yoshihiro (Clin Cancer Res, 2020)
PURPOSE: To examine effect of oncolytic herpes simplex virus (oHSV) on NOTCH signaling in CNS tumors. EXPERIMENTAL DESIGN: Bioluminescence imaging, RPPA proteomics, fluorescence microscopy, reporter assays, and molecular biology approaches were used to evaluate NOTCH signaling. Orthotopic glioma- mouse models were utilized to evaluate effects in vivo. RESULTS: 1. We have identified that HSV-1 (oncolytic and wild type) infected glioma cells induce NOTCH signaling from inside of infected cells into adjacent tumor cells (inside out signaling). This was canonical NOTCH signaling which resulted in activation of RBPJ dependent transcriptional activity that could be rescued with dnMAML. 2. High-throughput screening of HSV-1-encoded cDNA and micro-RNA libraries further uncovered that HSV-1 miR-H16 induced NOTCH signaling. We further identified that factor inhibiting HIF-1 (FIH-1) is a direct target of miR-H16, and that FIH-1 downregulation by virus encoded miR-H16 induces NOTCH activity. 3. FIH-1 binding to Mib1 has been reported, but this is the first report that shows FIH-1 sequesters Mib1 to suppress NOTCH activation. We observed that FIH-1 degradation induced NOTCH ligand ubiquitination and NOTCH activity. Rembrandt and TCGA data analysis also uncovered a significant negative regulation between FIH-1 and NOTCH. 4. Furthermore, combination of oHSV with NOTCH blocking GSI had a therapeutic advantage in two different intracranial glioma models treated with oncolytic HSV, without affecting safety profile of the virus in vivo. CONCLUSION: To our knowledge this is the first report to identify impact of HSV-1 on NOTCH signaling and highlights the significance of combining oHSV and GSI for glioblastoma therapy.